Case Report: Life-threatening hypercalcemia associated with MMR-deficient endometrial carcinoma secreting parathyroid hormone - Liu, Huazhen; Gao, Dan; Huang, Yongfa; Li, Ji; Zhao, Mengyun; Lu, Zhaohui; Hu, Ya; Wang, Tao; Zhang, Yingqiang; Wang, Wenze; Cao, Dongyan (Frontiers in Endocrinology, 2023)
Ectopic secretion of parathyroid hormone (PTH) is a rare cause of hypercalcemia in malignancy patients. A 56-year-old woman with life-threatening hypercalcemia was caused by poorly-differentiated endometrial carcinoma secreting PTH with concomitant nodular goiter mimic parathyroid tumors. The elevated level of PTH and calcium decreased immediately after cytoreductive surgery (CRS). The pathology confirmed mismatch repair (MMR)-deficient endometrial carcinoma with PTH expression. The patient received four-course chemotherapy and one-course immunotherapy after CRS. The disease progression led to multiple organ failure and death about five months after CRS. To our knowledge, this is the first case of hypercalcemia caused by MMR-deficient endometrial carcinoma with ectopic PTH secreting and the first report of malignancy associated hypercalcemia complicated with nodular goiter.